2012
DOI: 10.1039/c2mt20050c
|View full text |Cite
|
Sign up to set email alerts
|

The importance of adding EDTA for the nanopore analysis of proteins

Abstract: Nanopore analysis is a promising technique for studying the conformation of proteins and protein/protein interactions. Two proteins (bacterial thioredoxin and maltose binding protein) were subjected to nanopore analysis with α-hemolysin. Two types of events were observed; bumping events with a blockade current less than -40 pA and intercalation events with blockade currents between -40 pA and -100 pA. In potassium phosphate buffer, pH 7.8, both proteins gave intercalation events but the frequency of these even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…In most cases, this process would generate bumping events. By analyzing the duration and current distributions of the bumping events, the a-HL achieved the detection of single molecule behavior of the analytes of a large size, such as illuminating the interactions between prion proteins and metal ions 52,53 and analyzing the aggregation states of peptides. [54][55][56] A previous study showed that the aggregation states of bamyloid 42 (Ab42) could be analyzed by monitoring the bumping events using an a-HL nanopore (Fig.…”
Section: Analysis Of the Bumping Events In Nanopore Detectionsmentioning
confidence: 99%
“…In most cases, this process would generate bumping events. By analyzing the duration and current distributions of the bumping events, the a-HL achieved the detection of single molecule behavior of the analytes of a large size, such as illuminating the interactions between prion proteins and metal ions 52,53 and analyzing the aggregation states of peptides. [54][55][56] A previous study showed that the aggregation states of bamyloid 42 (Ab42) could be analyzed by monitoring the bumping events using an a-HL nanopore (Fig.…”
Section: Analysis Of the Bumping Events In Nanopore Detectionsmentioning
confidence: 99%
“…Most reports show that proteins induce large blockade events when interacting with the α-hemolysin pore [4], [5], [7], [40], [41], [42], [43]. We have analyzed eight different proteins (unpublished data) using alpha-hemolysin and all induce large blockade events.…”
Section: Introductionmentioning
confidence: 99%
“…At the first glance, the profile of the events observed are similar to those obtained with small peptides and single-stranded DNA or RNA which can be mistakenly identified as translocation events. However, most proteins analyzed with nanopore sensing are larger than the smallest constriction of the α-hemolysin pore [2], [5], [7], [8], [10], [14], [15], [17], [43], [44]. Therefore, in order for proteins to translocate the pore, they must unfold.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, nanopores can, in principle, provide precise information on a single-molecule level. Significant efforts have been devoted to nanopore DNA sequencing [2] and only recently possible proteomic applications have started being explored [3][4][5][6][7][8][9][10][11][12] using both solid-state and biological pores.…”
Section: Introductionmentioning
confidence: 99%